Is ovarian cancer surgery stuck in the dark ages?: a commentary piece reviewing surgical technologies - Phelps, David L. (Br J Cancer, 2020)
Ovarian cancer surgery endeavours to remove all visible tumour deposits, and surgical technologies could potentially facilitate this aim. However, there appear to be barriers around the adoption of new technologies, and we hope this article provokes discussion within the specialty to encourage a forward-thinking approach to new-age surgical gynaecological oncology.